The integration of women and the effects of the “glass ceiling” in the police profession - Tomić Marta (Temida, 2012)
This paper considers the position of women in the police profession in terms of domination of masculinity and the effects of the “glass ceiling”. Generally, these mechanisms create unequal opportunities and unequal treatment of women in the police and other predominantly male professions, and overall create adverse conditions for their integration and slower career advancement. The aim of this paper is to show that women who are employed in the police, who have an affinity for the profession and wish to advance professionally are socially conditioned in a predominantly male environment, particularly in professions that have a historically bounded rule of masculinity, and that, as such, the mechanisms of the “glass ceiling” prevent them to reach the highest step in their career. Women in the police profession still are still a minority and have to deal with well integrated social and professional structural barriers as well as cultural barriers.